englishREGENERATIVE TOURISM IN THE COMMON POLL RESOURCES (CPRS): CONSERVATION VILLAGE MODEL (MKK) CISANGKU-MALASARI VILLAGE OF GUNUNG HALIMUN SALAK NATIONAL PARK (TNHGS) - Yuwana Marjuka; Nukeu Novia Andriani; Teguh Hartono (Fakultas Pariwisata Universitas Pancasila, 2024)
Cisangku-Malasari Village is a tourist destination that represents regenerative tourism in certain tourist destinations. The people of Cisangku-Malasari Village in the TNGHS area are people who have lived and depended on the surrounding forest nature for generations. Cisangku-Malasari Village as part of the TNHGS is a public goods. Regenerative tourism understands that visitors and destinations are part of a living system embedded in the natural environment, and operate under the rules and principles of nature. This study aims to investigate the implementation of regenerative tourism programs. The purpose of this study is to identify activities to rejuvenate the environment and natural landscape in Cisangku-Malasari village as a public good in the TNHGN area. This research uses descriptive analysis research method. This research uses a method of literary study by studying and comparing the content of a book, research results of a scientific article or journal, news, and also reports that correspond to the theory that will be discussed in particular in the field of regenerative tourism and sustainable tourism. The results of the study found that regenerative tourism at Cisangku-Malasari village is still far from successful although it is a good program. The regenerative tourism indicator is that there is still a far from sustainable manner.